The influence of health education on increasing female students' knowledge of BSE at Yaspim Patompo University - Mustafa, Sri Resky; Nea, Hugolina; Thalib, Abdul (CV. Paperhome Indonesia, 2024)
Background: The incidence of breast cancer increases with age; however, being young does not guarantee immunity from breast cancer. The highest incidence rate for women is breast cancer, at 42.1 per 100,000 population, with an average mortality rate of 17 per 100,000. Breast cancer symptoms can be detected early if women of reproductive age perform breast self-examinations (BSE) correctly. Method: This study employs a quantitative research design with a one-group pre-test and post-test approach. The sample consisted of 40 respondents, and data were analyzed using the Wilcoxon test. Results: The study results show a p-value of 0.000 (<0.05), indicating a significant effect of health education on students' knowledge about BSE at Yaspim Patompo University. Conclusion: Health education on BSE can be conducted continuously among female students to prevent the rising incidence of breast cancer and improve the quality of life for adult women. Activities that enhance knowledge about breast self-examinations are recommended so that women of reproductive age can practice them as an early detection measure for breast cancer in their daily lives.